OPTIMIZING THE CEATIVE BUSINESS INDUSTRY OF WOOD-WASTE CRAFT PRODUCTS - Nurhayani, Ulfa; Zainal, Andri (Universitas Negeri Medan, 2019)
The implementation of activities focused on updating production and e-commerce management on œBorna aims at resolving some of the challenges and obstacles experienced by Borna. One of them is in the production stage, where wood cutting still uses a jigsaw, making production processes longer and limiting e-commerce that still relies on social media platforms, making marketing networks and sales levels still low. The assistance program to facilitate the resolution of the problem in question was carried out at the end of August 2019, in Binjai. In addition, on the same occasion, appropriate technology assistance was also carried out by handing over a saw machine for efficiency and effectiveness in the process of cutting round, hexagonal and trapezium wood plates. As a complement in updating partner competencies, the implementation team also provides training and assistance in developing the website as one of the main e-commerce platforms to increase partner marketing and revenue. The use of e-commerce websites in expanding market share slowly but surely has made Borna products become more exposed and known and can compete with products originating from Java Island which currently dominate national and international market share. Keywords: Craft Products; Souvenir Wood Waste; Borna; Binjai.